2011
DOI: 10.1074/jbc.m110.208587
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Susceptibility Polymorphism of p53 at Codon 72 Affects Phosphorylation and Degradation of p53 Protein

Abstract: The common polymorphism of p53 at codon 72, either encoding proline or arginine, has drawn attention as a genetic factor associated with clinical outcome or cancer risk for the last 2 decades. We now show that these two polymorphic variants differ in protein structure, especially within the N-terminal region and, as a consequence, differ in post-translational modification at the N terminus. The arginine form (p53-72R) shows significantly enhanced phosphorylation at Ser-6 and Ser-20 compared with the proline fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The Arg/Pro genotype of p53 codon 72 singly as well as in combination with Pro/Pro genotypes conferred protection towards oral cancer development. There are evidences that the codon 72 polymorphism had a profound effect on the primary structure of p53 protein and its biochemical and biological activities (Matlashewski et al, 1987;Ozeki et al, 2011). It has been shown that the Pro-72 form of p53 has increased transcriptional trans-activation capacity, induces a higher level of G1 arrest and senescence compared to the Arg-72 form (Thomas et al, 1999;Pim and Banks 2004;Frank et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Arg/Pro genotype of p53 codon 72 singly as well as in combination with Pro/Pro genotypes conferred protection towards oral cancer development. There are evidences that the codon 72 polymorphism had a profound effect on the primary structure of p53 protein and its biochemical and biological activities (Matlashewski et al, 1987;Ozeki et al, 2011). It has been shown that the Pro-72 form of p53 has increased transcriptional trans-activation capacity, induces a higher level of G1 arrest and senescence compared to the Arg-72 form (Thomas et al, 1999;Pim and Banks 2004;Frank et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The p53 polymorphic variants p53Pro and p53Arg differ in regulating the p53 dependent cell processes, such as a cell cycle arrest, DNA repair, programmed cell death induction, aging, and hypoxia resistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…20), RIN (rat pancreatic β cell), and MIN6 (mouse pancreatic β cell). Cell culture and transfection was performed as described (21). The siRNAs were introduced using RNAiMAX (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%